ETIKA ILMIAH ISLAM SEBAGAI WUJUD TOLERANSI (Analisis Pemikiran Taha Jabir al-Alwani dalam Kitab Adab al-Ikhtilafi fi al Islami) - M. Ulil Abshor; Husnul Khotimah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
The rise of change and the behavior of society today change the distortion or differences in factors, news, and issues those are freely scattered in the mass media are no longer heard by the Indonesian people, so it becomes the people's consumption that is swallowed raw so that it starts to fix it. When people take news and information about and direct then many questions arise, it is appropriate, but the problem is all the news that comes from the mass media used to criticize and disbelieve others, this causes a variety of differences that result in the decline of humans to be able to support each other and make a difference as a mercy for all nature. All kinds of actions that cause conflict and friction between human beings are triggered by negative ideological reasoning that challenges its truth. Because reason and ideology that are formed do not show a more wise view and behavior in responding to differences. Therefore, the author wants to discuss more deeply about ethical knowledge and scientific knowledge of scientific ethics capable of realizing a tolerant attitude and understanding perspective. Of course, this author uses the Content Analysis method as the main reference in examining the views of Taha Jabir al-Alwani about attitudes and actions relating to science using interpretive-descriptive methods. Then the results obtained from scientific ethics are resolved (1). Self-awareness consists of magical, naive, critical, and transformative awareness,(2). Social awareness consists of mutual support, compilation, understanding, (3). Revolution awareness and (4). Divine Awareness is a difficult challenge to avoid because of hostility, strife, strife, termination of akin relations which is opposed by Allah.